Pengaruh Dosis Probiotik Lactobacillus plantarum pada Pakan terhadap Pertumbuhan Berat Mutlak Udang Vannamei Litopenaeus vannamei Skala Laboratorium DOC 33 Pemeliharaan - Hadaitana Sandy; Didik Budiayanto; Achmad Kusyairi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study aims to analyze the effect of probiotic Lactobacillus plantarum supplementation in artificial feed at different dosages on the absolute weight growth of vannamei shrimp (Litopenaeus vannamei) at laboratory scale DOC 33. The research employed an experimental method using a Completely Randomized Design (CRD) consisting of four treatments and six replications, resulting in 24 experimental units. The treatments included probiotic dosages of 100 ml/kg, 150 ml/kg, 200 ml/kg, and 250 ml/kg of feed. Shrimp were maintained with feeding three times daily, and water quality parameters such as temperature, pH, salinity, and dissolved oxygen (DO) were regularly monitored. Data were analyzed using ANOVA followed by Least Significant Difference (LSD) test when significant differences were detected. The results showed that different probiotic dosages had a highly significant effect on shrimp growth (p<0.01). The highest growth was observed at 100 ml/kg feed with an average value of 4.96±0.17, while the lowest was at 150 ml/kg with 4.39±0.49. Water quality parameters remained within optimal ranges throughout the study. Therefore, the use of Lactobacillus plantarum as a probiotic in feed can enhance the growth performance of vannamei shrimp, although its effectiveness depends on the dosage applied.